Nursing orientation given to children in antineoplastic chemotherapy treatment - Elaine Freire Cruz; Liliane Faria da Silva; Fernanda Garcia Bezerra Goes; Rosane Cordeiro Burla Aguiar; Juliana Rezende Montenegro Medeiros de Moraes (Universidade Federal de Goias, 2014)
A qualitative descriptive study carried out in a public pediatric hospital using semi-structured interviews with nine nursing professionals. It aims to identify orientation given by the nursing staff to school-aged children regarding antineoplastic chemotherapy and the aspects which difficult and facilitate such orientation. The results point to the fact that children receive little information about the side effects of their treatment, for all other information is directed to parents. The child's relationship with their peers and family members facilitates orientation and such relationship serves as a mediator for better acceptance of treatment on the child's behalf. The fact that the children do not understand the language used by nursing professionals during orientation was pointed out as a hindering factor. In conclusion, professionals recognize that children are capable of understanding the given orientation, but find it difficult to communicate with them using accessible language, in accordance with the child's development. doi: doi: 10.5216/ree.v16i2.27009.